The Bitter Taste Masking of Sour Lime (Citrus aurantiifolia) Peel Extract using Β-Cyclodextrin Complex - Desmiaty, Yesi; Sandhiutami, Ni Made Dwi; Engita, Elvira; Irtan, Levina Diva; Noor, Siti Umrah (Integrated Research and Testing Laboratory (LPPT) Universitas Gadjah Mada, 2025)
Sour lime (Citrus aurantifolia) is widely used in Indonesia for beverages and herbal remedies, but the bitterness of its peel limits its application in nutraceuticals. This study aimed to mask the bitter taste of sour lime peel (SLP) extract using β-cyclodextrin (β-CD) to form inclusion complexes. SLP was extracted with 70% ethanol via ultrasonication, then combined with β-CD at different ratios: Ci1 (0.5:2), Ci2 (0.75:2), and Ci3 (1:2), and freeze-dried. The resulting complexes were evaluated for antioxidant activity (DPPH assay) and physicochemical characteristics (bitterness value, FT-IR, SEM, XRD, and DSC). XRD and SEM analyses confirmed all inclusion complexes' amorphous and irregular structures, indicating successful encapsulation. Ci1 and Ci2 showed no detectable bitterness, while Ci3 and the crude extract exhibited bitterness values of 5 and 9 units/g, respectively. FT-IR showed the absence of ester group peaks in Ci1, and DSC indicated a shift in the endothermic peak, supporting complex formation. Among the formulations, Ci2 demonstrated the best performance in masking bitterness while retaining antioxidant activity. These results suggest that β-CD inclusion complexes, particularly Ci2, effectively improve the palatability of SLP extract and are suitable for further development in functional beverages and nutraceutical products.